Essentials of eccentric training - Kravitz, L.; Bubbico, A. T. (Human Kinetics, 2015)
Eccentric training provides greater intensity to help individuals push past plateaus and increase muscular strength, endurance and power backed by evidence-based studies and incorporated into training programmes. This innovative approach to resistance training and conditioning produces extraordinary results.This is the first comprehensive resource to cover this innovative approach to resistance training and conditioning that produces extraordinary results. Backed by evidence-based studies and readily incorporated into training programmes, eccentric training provides greater intensity to help individuals push past plateaus and increase muscular strength, endurance and power. Using this method, strength and conditioning professionals and personal trainers can also help their clients improve metabolism, manage their weight and facilitate injury rehabilitation. Chapter 1. Understanding Muscular Structure and the Physiological Mechanisms of Concentric and Eccentric Action; Chapter 2. Discovering the Eccentric Training Methods; Chapter 3. Boosting the Metabolism With Eccentric Exercise; Chapter 4. Eliminating Muscle Soreness With the Repeated Bout Approach; Chapter 5. Eccentric Training for Strength; Chapter 6. Eccentric Training for Endurance; Chapter 7. Eccentric Training for Explosive Power; Chapter 8. Eccentric Training for Weight Loss; Chapter 9. Eccentric Training for Muscle Hypertrophy; Chapter 10. Eccentric Exercise and Rehabilitation.